Breadfruit Flour, Food to Lower Blood Sugar Levels in Mice Model Diabetes Mellitus - Martha Kaihena; Abdul Mahid Ukratalo; Maria Nindatu; Deford Christy Birahy (Syntax Corporation Indonesia, 2023)
Consumption of foods with high amylose content (>25%) as well as a low glycemic index (<55) is able to improve the insulin sensitivity of people with diabetes mellitus. Breadfruit has in about 23-60 which means that breadfruit is safe to consume. The purpose of this research is to find out the levels of reduced sugar, amylose, and blood sugar levels mice after being fed breadfruit flour. This research used a Complete Randomized Design using 5 treatments namely normal control group (KN), negative control (K-), positive control (K+), STZ + breadfruit flour dose 5 g (P1) and STZ + breadfruit flour dose 10 g (P2). Breadfruit is taken and then processed into breadfruit flour, after which testing of reduced sugar content and amylose breadfruit flour. Before treatment, all mice were measured for initial glucose levels. After that in groups K (-), K (+), P1, and P2 injected STZ on days 1, 2, and 3. After 3 days, the blood glucose level (post-STZ) was measured again, then compared to the blood glucose level on the first day before being given STZ. If there is an increase in blood glucose levels of mice that is to ±128 mg / dL then mencit is considered to be diabetic. Then in group K (+) drug given Metformin, P1 and P2 were fed breadfruit flour with a predetermined dose for 7 days. The results showed that the sugar content of reduced breadfruit was cut by 3.26%. While the level of amylose in breadfruit flour is 19.3%. Breadfruit flour can also lower the sugar content of mice.